2011
DOI: 10.1161/circinterventions.110.958884
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Patients With the Concomitant Use of Clopidogrel and Proton Pump Inhibitors After Percutaneous Coronary Intervention

Abstract: Background— The concomitant use of proton pump inhibitors (PPIs) with clopidogrel is suspected to be associated with an adverse impact on clinical outcomes in patients with coronary artery disease. We sought to evaluate whether the use of PPIs with clopidogrel was associated with worse clinical outcomes after percutaneous coronary intervention (PCI) compared with the use of clopidogrel alone. Methods and Results— We studied 2651 consecutive patients dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 29 publications
1
51
0
2
Order By: Relevance
“…Several professional organizations such as the American Heart Association and the American College of Gastroenterology have recommended that a proton pump inhibitor (PPI) should be used with anti-platelet therapy consisting of clopidogrel alone or clopidogrel and aspirin for gastrointestinal protection 5 . However, evidence from mechanistic studies has indicated that the anti-platelet effect of clopidogrel is reduced in the presence of PPIs because PPIs inhibit CYP2C19, an enzyme responsible for the conversion of clopidogrel to its active metabolite [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Several professional organizations such as the American Heart Association and the American College of Gastroenterology have recommended that a proton pump inhibitor (PPI) should be used with anti-platelet therapy consisting of clopidogrel alone or clopidogrel and aspirin for gastrointestinal protection 5 . However, evidence from mechanistic studies has indicated that the anti-platelet effect of clopidogrel is reduced in the presence of PPIs because PPIs inhibit CYP2C19, an enzyme responsible for the conversion of clopidogrel to its active metabolite [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…10 The strongest evidence for such an interaction is between omeprazole and clopidogrel, attributed to the fact that this PPI has a high potential to inhibit the CYP2C19 isoenzyme and thus modulate conversion of clopidogrel into its active metabolite. Previously, several observational studies 10,[15][16][17][18][19][20][21][22][23][24][25][26]29,34,35 and 1 prospective randomized trial 36 found conflicting results with respect to the association between concomitant PPI and clopidogrel use and the risk of cardiovascular outcomes. In contrast to clopidogrel and another thienopyridine, prasugrel, ticagrelor is a P2Y12 inhibitor that does not require biotransformation and has no known pharmacokinetic or pharmacodynamic interaction with PPIs.…”
mentioning
confidence: 99%
“…4,10 In contrast, ticagrelor is a directly acting P2Y12 inhibitor not requiring biotransformation 12,13 and with no known interaction with PPIs. 14 In view of the ongoing debate regarding the clinical significance of the interaction between clopidogrel and PPIs, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] we examined the relationship between PPI use and cardiovascular outcomes in patients with ACS randomized to clopidogrel or ticagrelor in a prespecified, nonrandomized subgroup analysis of the Platelet Inhibition and Patient Outcomes (PLATO) trial. 30,31 …”
mentioning
confidence: 99%
“…The question still remains unanswered, however, and larger studies that are adequately powered to examine outcomes such as stent thrombosis and gastrointestinal bleeding need to be conducted to fully reassure the clinician. 3 …”
Section: Discussionmentioning
confidence: 99%